Expression of adaptation potential by cultivars of highbush blueberry when introduced to Belarusian Polesia - Kurlovich Tatyana V. (EDP Sciences, 2021)
Highbush blueberry is a group of endemic species from North America. Its introduction to Belarusian Polesia is associated with transfer of cultivars of this group into an environment with a harsher climate. Adaptive capacity of highbush blueberry allowed its cultivars to adapt to the new environment, fully develop their fruits and complete their vegetation cycle. The property of the plants to fully utilize the time of their vegetation period manifested as shortening of the completion of the main phenophases due to the influence of the temperature factor. In an introduced environment the speed of the phenophases significantly depended on the peak day temperatures, which allowed the cultivars to successfully develop their fruits in an environment where they don’t receive sufficient heat during the vegetation period, as well as to complete the vegetation cycle.